The Influence of Learning Models on Ability Solving Pollution Matter Problem Environment in SMPN 1 Rantau Utara - Kurnia Putra Kurnia Putra (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2022)
The purpose of this study was to determine the effect of the problem based learning , everyone is a teacher here , and expository learning model on the problem solving ability of students in biology lessons on environmental pollution at SMPN 1 Rantau Utara. The population of this study was all students of class VII SMPN 1 Rantau Utara totaling 373 students consisting of grades VII 1 to VII 9 . The sample of this research was taken by using cluster random sampling technique as many as 3 classes, each class consisted of 34 students. Class A as problem based learning class, class B as class everyone is a teacher here, and class C as the expository class. The data collection instrument for students' problem solving abilities was used to test the description of environmental pollution material. The data analysis technique used covariate analysis technique (ANACOVA) with =0.05. The results obtained are the results of covariate analysis showing that the learning model has a significant effect on problem solving abilities (F=414,239; P=0.000). The average problem-solving ability of the problem-based learning class has an effect of 3.3, which is higher than the class everyone is a teacher here and 34.18, which is higher than the expository. Class everyone is a teacher here to give the effect of 30.88 higher than expository. It can be concluded that there is a significant effect of the problem-based learning model and everyone is a teacher here on the problem-solving ability of students' biology lessons on environmental pollution at SMPN 1 Rantau Utara..